2012
DOI: 10.1007/978-3-642-31875-7_39
|View full text |Cite
|
Sign up to set email alerts
|

Service for Crowd-Driven Gathering of Non-Discoverable Knowledge

Abstract: Knowledge that cannot be discovered through automated methods, such as user practices, remains in informal mediums. It is unstructured, and in collective possession of the experts, yet it is key for business insights. Typically this "Non-Discoverable knowledge" is gathered in semi-automated way, which at best provides crude estimates, and doesn't scale. In this paper, we describe our novel approach to rapidly design a process solution for a family of business objects, gathering required knowledge through the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This is so primarily because internal crowdsourcing allows for the exposure of innovative ideas to wider audiences compared with such exposure in hierarchy-based work organisation (Bjelland and Wood, 2008). In addition to the immediate Gaspoz, 2011;Guy et al, 2015;Laredo et al, 2012;McAfee, 2006McAfee, , 2009Patten and Keane, 2010;Rohrbeck et al, 2015;Schlagwein et al, 2011;Simula and Vuori, 2012;Stocker et al, 2012; 2012 Bjelland and Wood, 2008) • May result in new products (e.g., Soukhoroukova, 2012), commercialisation of new technologies (e.g., Bjelland and Wood, 2008), or improvement to existing products and processes (e.g., Vuori, 2012) Bjelland andWood, 2008;Erickson et al, 2012a, b;Leung et al, 2014;Muller et al, 2013;Simula and Ahola, 2014;Simula and Vuori, 2012;Soukhoroukova, 2012;Standing and Kiniti, 2011 Choice…”
Section: Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is so primarily because internal crowdsourcing allows for the exposure of innovative ideas to wider audiences compared with such exposure in hierarchy-based work organisation (Bjelland and Wood, 2008). In addition to the immediate Gaspoz, 2011;Guy et al, 2015;Laredo et al, 2012;McAfee, 2006McAfee, , 2009Patten and Keane, 2010;Rohrbeck et al, 2015;Schlagwein et al, 2011;Simula and Vuori, 2012;Stocker et al, 2012; 2012 Bjelland and Wood, 2008) • May result in new products (e.g., Soukhoroukova, 2012), commercialisation of new technologies (e.g., Bjelland and Wood, 2008), or improvement to existing products and processes (e.g., Vuori, 2012) Bjelland andWood, 2008;Erickson et al, 2012a, b;Leung et al, 2014;Muller et al, 2013;Simula and Ahola, 2014;Simula and Vuori, 2012;Soukhoroukova, 2012;Standing and Kiniti, 2011 Choice…”
Section: Resolutionmentioning
confidence: 99%
“…Similarly, Deutsche Telekom launched an internal crowdsourcing initiative to integrate the knowledge and experience of its employees, resulting in more than 18,000 contributions collected and processed in just 4 days (Hoerbelt, 2013). Internal crowdsourcing also helps reveal 'non-discoverable knowledge' (Laredo et al, 2012), that is, collective, tacit or unstructured knowledge that could not be found through automated methods and systems (see further Vukovic and Stewart, 2012).…”
Section: Problems Addressed With Internal Crowdsourcingmentioning
confidence: 99%
See 1 more Smart Citation
“…To implement principles of collaborative knowledge discovery we employ system BizRay [7], a general-purpose, cloud-enabled, enterprise crowdsourcing self-service that expedites delivery of crowdsourcing campaigns to discover critical tacit business knowledge that is in collective possession of the experts. Knowledge requests are captured as a distributed questionnaire, which consists of one or more sections, each containing one or more questions.…”
Section: Enterprise Crowdsourcing Servicementioning
confidence: 99%